Prospective, multicenter validation of prediction scores for major bleeding in elderly patients with venous thromboembolism. Issue 3 (13th March 2013) - Scherz, N.; Méan, M.; Limacher, A.; Righini, M.; Jaeger, K.; Beer, H. ‐J.; Frauchiger, B.; Osterwalder, J.; Kucher, N.; Matter, C. M.; Banyai, M.; Angelillo‐Scherrer, A.; et al.
Summary Background The Outpatient Bleeding Risk Index (OBRI) and the Kuijer, RIETE and Kearon scores are clinical prognostic scores for bleeding in patients receiving oral anticoagulants for venous thromboembolism (VTE). We prospectively compared the performance of these scores in elderly patients with VTE. Methods In a prospective multicenter Swiss cohort study, we studied 663 patients aged ≥ 65 years with acute VTE. The outcome was a first major bleeding at 90 days. We classified patients into three categories of bleeding risk (low, intermediate and high) according to each score and dichotomized patients as high vs. low or intermediate risk. We calculated the area under the receiver‐operating characteristic (ROC) curve, positive predictive values and likelihood ratios for each score. Results Overall, 28 out of 663 patients (4.2%, 95% confidence interval [CI] 2.8–6.0%) had a first major bleeding within 90 days. According to different scores, the rate of major bleeding varied from 1.9% to 2.1% in low‐risk, from 4.2% to 5.0% in intermediate‐risk and from 3.1% to 6.6% in high‐risk patients. The discriminative power of the scores was poor to moderate, with areas under the ROC curve ranging from 0.49 to 0.60 (P = 0.21). The positive predictive values and positive likelihood ratios were low and varied from 3.1% to 6.6% and from 0.72 to 1.59, respectively. Conclusion In elderly patients with VTE, existing bleeding risk scores do not have sufficient accuracy and power to discriminate between patients with VTE who are at a high risk of short‐term major bleeding and those who are not.